An Enterprise Digital Right Management Scheme with Anonymous Trust for Mobile Devices - Yang, J.-H.; Sun, H.-M.; Chen, P.-L. (Informatica)
An Enterprise Digital Right Management Scheme with Anonymous Trust for Mobile Devices